PERLUNYA KERANGKA KONSEPTUAL AKUNTANSI BAGI SUATU NEGARA - Aida Nahar (Universitas Islam Nahdlatul Ulama Jepara, 2004)
Characteristic diversity of nations such a political environment, law order, culture etc. of course make different accounting practices among countries. This diversity prosecute there is a conceptual framework of accounting for those nations. It is needed in order to establish a constitution for resolving issues in setting accounting standard. A well-conceived and fully developed conceptual framework should consider each of the four tiers as well as the logical connections between tiers. This paper explain the conceptual framework and how to build this framework.